The Role of the Rector of a Major Seminary in the Light of the Challenges of the Contemporary World and the Formation Principles in Ratio Institutionis Sacerdotalis pro Polonia (2021) - Rabczyński, Paweł (Studia Warmińskie, 2022)
The article presents the role of the rector of a major seminary in the light of the challenges of contemporary world and formation principles in the Polish Bishops’ Conference document Ratio institutionis sacerdotalis pro Polonia from 2021. The rector’s assignments and qualities need to be perceived in the context of the role they play in the community of academics and students and not through the lense of their administrative position. The rector’s mission is ensuring that the formation process of presbyter candidates continues according to the requirement set by the Church. Ratio presents the rector as the coordinator of educational activities in managing the seminary. Their main task is supervising the verification of how educational purposes are accomplished by the students at each stage of their formation as well as during the scrutinies. Their other duty is the preparation of the statute, the formation law and the regulations of the seminary community and ensuring they are observed. Due to the tasks enlisted in Ratio the rector is expected to personify such qualities as prudence, wisdom, balance, solid background in theology and teaching and the ability to read the signs of the times and the challenges of the contemporary world.